An Analysis of the 'Bringout' Fashion Business Plan Through the Business Model Canvas Approach - Risma Agustiani; Sukma Nugraha; Asri Solihat (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
Bringout is a business operating in the fashion industry. Established in 2020, the company initially did not have a Business Model Canvas, which led to several issues in sales and marketing. This study aims to analyze the Business Model Canvas planning , which consists of nine building blocks: customer relationships , key partners , value proposition , customer segments , channels , revenue streams , key resources , key activities , and cost structure , in order to develop a new business model. The research method used is a qualitative case study approach. Several types of data are required for developing the business model. The first is the current business model, obtained through observation. The second is data collected by distributing questionnaires to consumers and individuals familiar with the Bringout product. Based on the analysis, one improvement made to Bringout's business model is in the customer segment , by targeting university students and employees aged 18 to over 35 years old. The analysis results highlight the importance of developing products that align with the defined target age group. As a result, several elements of the Bringout business were revised to foster innovation and improve sales performance.